Landslide environment in Pakistan after the earthquake-2005: information revisited to develop safety guidelines for minimizing future impacts - Tariq, Shahina; Gomes, Chandima (Omics Publishing Group, 2017)
The 2005 earthquake in Pakistan engraved one of the worst natural hazards in the history of mankind.The mass destruction caused by nature in several parts of Azad Jammu Kashmir is revisited to assess the public impact. Several visits were paid to the most affected areas of the region, especially Muzaffarabad, to collect data on debris flow patterns, loss of vegetation, instability of the surface structure and buildings, impacts on social structure etc. Influences of pre-slide activities, both natural and man-made, on the pattern of landslides and triggering factors were investigated. The major landslide catastrophe that took place in Attabad in January 2010 was discussed as a case study. Attempts were made to correlate observations elsewhere with collected data, pertinent to 2005 earthquake in Pakistan with the objective of proposing safety guidelines to prevent or at least minimize such human catastrophes in the future, in the case of such an event.